Revisiting the Zero-Leverage Puzzle: the Perspectives of R&D, Market Competition and Equity Financing - Li, S (2023)
This thesis investigates a puzzling finding in capital structure literature. A large proportion of firms absolutely eschew debt financing, leaving a substantial fraction of their value on the table by not taking the tax benefit. This phenomenon is becoming increasingly prevalent around the world.